Symptoms in Pectus Deformities: A Scoring System for Subjective Physical Complaints - Ewert, Franziska; Syed, Julia; Kern, Sonja; Besendörfer, Manuel; Carbon, Roman T.; Schulz-Drost, Stefan (Thoracic and Cardiovascular Surgeon, 2017)
Background The literature is silent on the relationship between symptoms and the Haller index. Nor is there a classification of the severity of the physical complaints. Materials and Methods Retrospectively, data from 128 patients (102 funnel, 25 pigeon chest patients, and 1 mixed type) were evaluated. To objectify the symptoms, we developed a score to describe the level of physical ailments. This score includes 10 different symptoms as well as the situation or frequency in which they occur and an impact factor. This depends on how much they affect everyday life. Results Pectus excavatum patients express physical complaints more frequently than pectus carinatum patients who actually suffer more from psychological stress. We could not find a correlation between the Haller index and symptoms or levels of ailment. Conclusion Pectus deformities are likely to cause physical and psychological complaints. Since the subjective symptoms did not show any correlation to the chest severity index, they are supposed to be independent from the deformity's extent.
EVALuna2:35787